Pengaruh Non-Performing Loan (NPL) dan Loan to Deposit Ratio (LDR) terhadap Kinerja Keuangan Perbankan - Weny Putri; Feby Astrid Kesaulya; Khairunnisa Khairunnisa (Faculty of Economics, Universitas Internasional Batam, 2021)
This study aims to identify whether financial ratios as measured by non-performing loans (NPL) and Loan To Deposit Ratio (LDR) have an effect on financial performance which is proxied by Net Interest Margin (NIM). The results of this study found that the level of bad loans or NPLs had a negative effect on financial performance. This is because the Bank's income does depend on the receipt of loan interest from the Customer. Meanwhile, LDR does not have a positive effect on financial performance with the assumption that a low LDR will cause the company's liquidity to increase and in the end it will also increase the quantity of idle funds which will have a direct impact on financial performance.